THE COMPARISON STUDY OF PROGRESSIVE MUSCLE RELAXATION THERAPY AND ENDORPHIN MASSAGE TOWARDS THE ANXIETY LEVEL OF 3rd TRIMESTER PREGNANT MOTHERS IN BPM LU'LUATUL MUBRIKOH BANGKALAN - Selvia Nurul Qomari; Nailufar Firdaus; Melya Rossa (NHM PRESS, 2020)
Anxiety is a feeling or reaction to danger that instinctively warns people and the person may lose control in the situation. Pregnant women are more susceptible to experiencing the anxiety, especially in the 3rd trimester because they’re going to face a labor. The purpose of this study was to determine whether there are differences of the anxiety level of 3rd trimester pregnant women after being given Progressive Muscle Relaxation therapy and Endorphine Massage. This study was a Quasy Experimental Research with Pretest-Posttest Non-Equivalent Control Group Design. The population used was 3rd trimester pregnant women (>27 week gestational age) who have an ANC examination at BPM Lukluatul Mubrikoh, S.ST and will be divided into 3 groups based on regional clusters namely Progressive Muscle Relaxation Therapy (ROP) group, therapeutic group Endorphin Massage, and control group. Pregnancy anxiety is measured using the Hamilton Anxiety Rating Scale (HARS) both before and after therapy. The results of the study mentioned that after therapy, pregnant women in the Progressive Muscle Relaxation group experienced moderate anxiety (61.53%). Similarly, in the control group, most of the pregnant women in the posttest measurement experienced moderate anxiety (69.23%). In contrast to the other group, the Endorphine Massage group where most experienced mild anxiety (61.53%. The statistical test using Anova One Way obtained a significance value of 0.04 which means there is a difference in the average of anxiety level between the Progressive Muscle Relaxation therapy group, Endorphine Massage group, and control group. Given the importance of calm in pregnant women especially before delivery, it is hoped that health workers can provide a continous training to pregnant women and families about non-pharmacological relaxation techniques to reduce anxiety experienced by pregnant women